Moral distress among nurses in a hospital setting during the covid-19 pandemic (Revista Contexto & Saúde, 2025)
Objective: To analyze moral distress among nurses working during the COVID-19 pandemic in a hospital setting. Methods: This qualitative, exploratory-descriptive study was conducted with 18 nursing professionals from a hospital located in the extreme south of Brazil. Data were collected between December 2020 and March 2021 through individual semi-structured interviews conducted via videoconference on Google Meet. All participants signed an informed consent form. Data were analyzed using discursive textual analysis. Results: Participants reported experiencing moral distress related to fear of exposure to and contamination by the virus, illness, terminal conditions, deaths due to COVID-19, the population’s disregard for protective measures, work overload, shortage or inadequacy of materials, and insufficient bed availability, among other factors. Conclusion: The findings contribute to a deeper understanding of the factors that cause moral distress among nurses working in hospital settings during the COVID-19 pandemic and may support the development of strategies to minimize its adverse effects on workers’ health.
Keywords: Nursing Practitioners; COVID-19; Coronavirus Infections; Mental Health; Pandemics